Multiple variants in 5q31.1 are associated with systemic lupus erythematosus susceptibility and subphenotypes in the Han Chinese population. (12th June 2017) - Wen, L.L.; Zhu, Z.W.; Yang, C.; Liu, L.; Zuo, X.B.; Morris, D.L.; Dou, J.F.; Ye, L.; Cheng, Y.Y.; Guo, H.M.; Huang, H.Q.; Lin, Y.; et al.
Summary: Background: A previous study provided evidence for a genetic association between PPP2CA on 5q31.1 and systemic lupus erythematosus (SLE) across multi‐ancestral cohorts, but failed to find significant evidence for an association in the Han Chinese population. Objectives: To explore the association between this locus and SLE using data from our previously published genome‐wide association study (GWAS). Methods: Single‐nucleotide polymorphisms (SNPs) rs7726414 and rs244689 (near TCF7 and PPP2CA in 5q31.1) were selected as candidate independent associations from a large‐scale study in a Han Chinese population consisting of 1047 cases and 1205 controls. Subsequently, 3509 cases and 8246 controls were genotyped in two further replication studies. We then investigated the SNPs' associations with SLE subphenotypes and gene expression in peripheral blood mononuclear cells. Results: Highly significant associations with SLE in the Han Chinese population were detected for SNPs rs7726414 and rs244689 by combining the genotype data from our previous GWAS and two independent replication cohorts. Further conditional analyses indicated that these two SNPs contribute to disease susceptibility independently. A significant association with SLE, age at diagnosis < 20 years, was found for rs7726414 ( P = 0·001). The expression levels of TCF7 and PPP2CA messenger RNA in patients with SLE were significantly decreased compared with those in healthy controls. Conclusions: This study found evidence for multiple associations with SLE in 5q31.1 at genome‐wide levels of significance for the first time in a Han Chinese population, in a combined genotype dataset. These findings suggest that variants in the 5q31.1 locus not only provide novel insights into the genetic architecture of SLE, but also contribute to the complex subphenotypes of SLE. Abstract : What's already known about this topic? Systemic lupus erythematosus (SLE) is a prototype multisystem autoimmune inflammatory disease involving genetic and environmental predisposing factors. Genome‐wide association studies have been performed to identify and confirm over 70 risk genes associated with SLE. What does this study add? This study confirmed two independent SLE association signals in 5q31.1, with genome‐wide levels of significance for the first time in a Han Chinese population. Significant and suggestive associations were revealed between clinical manifestations and genetic variants. Both TCF7 and PPP2CA are within the association interval and are very likely to be involved in the development of SLE. What is the translational message? The genetic variant in 5q31.1 contributes to the complex subphenotypes of SLE, which suggests that this variant can be a novel marker for SLE phenotypes. The expression levels of TCF7 and PPP2CA messenger RNA in patients with SLE were significantly decreased, which suggests that TCF7 and PPP2CA can be used as an auxiliary method for the diagnosis of SLE. Linked Comment:  Sarin. Br J Dermatol 2017; 177 :620–621